2021
DOI: 10.1016/j.braindev.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal cohort study of childhood MMR vaccination and seizure disorder among American children

Abstract: Background: Measles (rubeola) is a highly contagious infectious disease with significant morbidity/mortality. Measles-Mumps-Rubella (MMR) is a live-attenuated vaccine used in the United States (US) to prevent measles. This retrospective longitudinal cohort study evaluated childhood MMR vaccination and the risk of a seizure episode and seizure disorder. Methods: The Independent Healthcare Research Database (IHRD) composed of records prospectively generated from Florida Medicaid was analyzed using SAS to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Outcomes, as described in previous studies, were identified from International Code for Disease, 9th revision (ICD-9) codes for rubella-related diagnoses (code: 056xxx) documented on claims for the children examined in this study. [4][5][6][7] Laboratory data confirming rubella diagnoses was not available in the IHRD. The onset of rubella infection was assumed to be the date of service for the first claim in chronological order with a rubella diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Outcomes, as described in previous studies, were identified from International Code for Disease, 9th revision (ICD-9) codes for rubella-related diagnoses (code: 056xxx) documented on claims for the children examined in this study. [4][5][6][7] Laboratory data confirming rubella diagnoses was not available in the IHRD. The onset of rubella infection was assumed to be the date of service for the first claim in chronological order with a rubella diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The status of vaccination was determined for each cohort member examined from current procedural terminology (CPT) codes filed on claims, as described in previous studies. 4 , 5 Rubella vaccination (codes: 90706, 9947, W1942), MMR vaccine (codes: 90707, W1943), measles and rubella vaccine (codes: 90708, W1944), rubella and mumps vaccine (codes: 90709, W1945), measles, mumps, rubella, and varicella (MMRV) vaccine (code: 90710) were the CPT codes examined in this study. The vaccinated cohort examined in this study included only children receiving a single dose of MMR vaccine (codes: 90707, W1943) during the study period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described previously in great detail, the IHRD contains de-identified healthcare records from the Florida Medicaid system [ 12 - 18 ]. Unique recipient identifier codes for each person allow for linkage of their eligibility and claim records.…”
Section: Methodsmentioning
confidence: 99%